Pancreatic Cancer Heralded by Worsening Glycemic Control: A Report of Two Cases - Dimpi Desai MD; Devika Rao MD; Vineeth Sukrithan MD; Eleanor Weinstein MD; Akankasha Goyal MD; Ulrich Schubart MD (SAGE Publishing, 2017)
Pancreatic ductal adenocarcinoma is the third leading cause of cancer-related death in the United States. Since it is usually diagnosed at an advanced stage, its prognosis remains poor. The initial presentation varies according to the tumor location. The most common presenting signs are weight loss, jaundice, and pain. Several epidemiological, clinical, and experimental studies over the past 2 decades have shown that long-standing diabetes is a modest risk factor for pancreatic cancer. However, new-onset diabetes has also been observed to be an early manifestation of pancreatic cancer. We report 2 cases where worsening glycemic control led to the diagnosis of pancreatic cancer.